Efektivitas Manajemen Intensifikasi Penguatan Pendidikan Karakter Melalui Pembelajaran dalam Jaringan (Daring) pada Masa Pasca Pandemi Covid 19 di SMAN 1 Gegesik Kabupaten Cirebon - Agus Salim (Departement of Mathematics Education, 2023)
The Covid-19 pandemic has had quite a big impact on the lives of Indonesian people, one of which is in the aspect of education. The policy regarding the implementation of learning in Indonesia is that learning must be carried out online or remotely. As the Covid 19 pandemic continues to spread, it has an impact on education, especially on the character and learning system of students. So every educational institution needs program management to strengthen character education. This study aims to understand the management of character education strengthening programs through online and offline learning during the Covid 19 New Normal pandemic which includes planning, implementation and evaluation.